Firm heterogeneity and the labour market effects of trade liberalisation - Hartmut Egger; Udo Kreickemeier (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper develops a model that incorporates workers' fair wage preferences into a general equilibrium framework with monopolistic competition between heterogeneous firms à la Melitz (2003). By assuming that the wage considered to be fair by workers depends on the productivity and thus the economic success of the firm they are working in, we can study the determinants of profits, involuntary unemployment and within-group wage inequality in a unified framework. We use this model to investigate the effects of globalisation. In a benchmark case with identical costs of entering domestic and foreign markets, there are gains from trade accompanied by distributional conflicts, which have so far not been accounted for in the literature: a simultaneous increase of average profits and involuntary unemployment as well as a surge in within-group wage inequality.
Keywords: F12; F15; F16; 330; Lohnstruktur; Arbeitslosigkeit; Globalisierung; Außenhandelsliberalisierung; Lohnpolitik; Gerechtigkeit; Allgemeines Gleichgewicht; Monopolistischer Wettbewerb; Theorie